ST2 regulates bone loss in a site-dependent and estrogen-dependent manner - Macari, Soraia; Madeira, Mila F. M.; Lima, Izabella L. A.; Pereira, Thais S. F.; Dias, George J.; Cirelli, Joni A. [UNESP]; Molon, Rafael S. de [UNESP]; Fukada, Sandra Y.; Szawka, Raphael E.; Garlet, Gustavo P.; Teixeira, Mauro M.; Silva, Tarcilia A. (Wiley-Blackwell, 2018)
Interleukin-33 (IL-33) and its receptor, ST2, are implicated in bone remodeling. The lack of estrogen after menopause results in an accelerated bone loss. Here we investigated the role of ST2 in the bone loss induced by estrogen deficiency. ST2-deficient mice (ST2(-/-)) and their littermates (wildtype [WT]) were ovariectomized (OVX), while ovary-intact mice were used as controls. Bone sites were analyzed by microcomputed tomography, histomorphometry, and quantitative real-time polymerase chain reaction (qPCR). Deletion of IL-33 or ST2 resulted in a similar bone loss in the femur and maxilla. Ovariectomy in WT mice caused bone loss in the same areas. The lack of ST2 in OVX mice did not alter bone remodeling in the femur but prevented bone loss in the maxilla. Consistently, ovariectomy increased the IL-33 messenger RNA (mRNA) levels in the maxilla but not in the femur. Under mechanical stimulation, ovariectomy and ST2 deletion independently increased bone remodeling induced by orthodontic tooth movement, which was also associated with a greater number of osteoclasts and a reduced number of osteoblasts in the maxillary bone. ST2(-/-) OVX mice, however, displayed twice as many osteoblasts as that of WT OVX mice. Ovariectomy and ST2 deletion differently altered the cytokine mRNA levels in the maxilla. Remarkably, interleukin-10 expression was decreased in both WT OVX and ST2(-/-) mice, and this reduction was completely restored in ST2(-/-) OVX mice. The results demonstrate that estrogen and IL33/ST2 independently protect against bone loss. However, the ovariectomy-induced bone loss is IL-33/ST2-dependent in the maxilla but not in the femur, indicating a bimodal and site-specific role of ST2 in bone remodeling.
Keywords: alveolar bone loss; estrogens; interleukin-33; maxilla; osteoporosis; site specific; ST2